Light Antinuclei from the Laboratory to the Cosmos. (2nd January 2022) - Bellini, Francesca
Abstract: The antiproton was experimentally discovered at the Bevatron, Berkeley, in 1955, earning Segré and Chamberlain the 1959 Nobel Prize in Physics. After that, light antinuclei, bound states of antiprotons and antineutrons, have been observed in high-energy interactions in the laboratory from antideuteron to antihelium-4 [1]. In nature, antinuclei are extremely rare objects to be found. The search for antinuclei in space has received considerable attention in recent years, following the suggestion that cosmic antinuclei might be produced in the annihilation or decay of dark matter (DM) particles [2 ]. Alternatively, "secondary" antinuclei could be produced in ordinary high-energy interactions of primary cosmic rays with the interstellar matter in our galaxy. A precise assessment of the background constituted by secondary antinuclei is pivotal for these searches and for the interpretation of the results. The spectrum of antiprotons observed in cosmic rays is consistent with the hypothesis of secondary production. No evidence of primary antiprotons, antihelium, and antideuterons has been found in the cosmic radiation so far. It is clear that the study of the formation of composite antimatter objects cannot but rely on samples of antimatter produced in the laboratory. Comprehensive measurements of different nuclear (and hypernuclear 1 ) species are necessary to meaningfully constrain formation models and require large data samples to be inspected, as the production of nuclear clusters becomes rarer with increasing mass number. Additional fundamental constraints to the production models are obtained from systematic studies of different particle sources, from proton–proton (pp) to heavy-ion collisions, where the size of the system can be experimentally controlled based on the number of particles (multiplicity) produced in the collision.